ANALISIS KONSEP DASAR ISLAM PADA PEMBELAJARAN SAINS DI MADRASAH IBTIDAIYAH KELAS IV (FISIKA & BIOLOGI) - Dibrina Raseuki Ginting; Syafira Aini Beru Ginting; Zikraul Husna; Veni Veronica Siregar; Nurul Aflah (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
The concept of learning that is arranged in the world of education is very influential in order to arrive at the goals that have been determined. The application of learning must be structured in such a way that the expected learning process runs. The Learning Process Design (RPP) is a benchmark for an educator when carrying out learning, the RPP that is formed must have conformity to the learning content carried out by the educator and here the author designs a lesson plan for class IV Madrasah Ibtidaiyah. The writing method uses a literature review of several trusted sources of scientific articles. The results obtained in this paper are the implementation of the basic concepts of Islam in Science subjects (Physics and Biology) which in the lesson plans are developed materials that combine Science subjects with religious science and combine the two, so that students are not only required in the cognitive domain but students also know Science from spiritual aspect and being able to be grateful for what they have and can apply the meaning of the verse that has been written in the Qur'an Surah Al-An'am: 99 teaches humans about the natural resources that God has given to humans and how to manage them.Keywords: Basic Concepts of Education, Science Learning, Madrasah Ibtidaiyah